Pre-competitive anxiety and role of achievement motivation on playing performance - Antony, V. C.; Tomar, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Anxiety and Motivation are important psychological variables in sports and it is needed to achieve high level of competition. Taylor (1994) treated motivation as the base of a pyramid towards success in sports. The elements of anxiety have a major influence in the athlete`s performance in any sport. Authors examined relationship of sports pre-competition trait anxiety & achievement motivation on football performance. Methods: Sixty football players (M age = 22.6 years) were selected as subjects, who played divisional football tournament at Jabalpur, India. Sports Competition Anxiety Test (Martens 1977) & Sports Achievement Motivation Test (Kamlesh 1990) were administered few hours and one day prior to the tournament respectively to collect data. As per SCAT scores, players were divided into moderate level and high level anxiety groups. Football playing performance was assessed by using a subjective evaluation chart prepared by soccer experts. Results: Pearson Product Moment Correlation found significant relationship between achievement motivation & football playing performance (r=0.367, p<.05). A positive relationship was established between pre-competitive moderate anxiety level players & playing performance (r=0.348, p<.05); and negatively related with pre-competitive high anxiety level players & football playing performance (r=-0.139, p<.05). Discussion: Football players showed significantly high level of achievement motivation towards playing performance (r=0.367, p<.05) which is supported by (Dureha et al., 2010; Unierzyski, 2003; Butt&Cox, 1992) who had noticed achievement motivation is one of the attributes of higher performance. Moderate anxiety level players shown positive relationship towards performance (r=0.348, p<.05) which endorses findings of (Bawa, 2001) that higher level performance group has moderate level of anxiety than the low level performance group. High anxiety level players had negative relationship with performance (r=-0.139, p<.05). If anxiety is not handled well or misinterpreted, athlete will lose control and their performance will decrease (Martens et al. 1990; Gualberto & Wiggins, 2008).